Legal Reform of Mediation Towards Fair Industrial Conflict Resolution - Kristiani, Enny; Santiago, Faisal (Green Publisher Indonesia, 2024)
Legal reform of mediation in the resolution of industrial conflicts is a crucial concern given the increasing complexity of disputes between workers and employers. The mediation process, which is expected to serve as an effective and fair middle ground, often encounters obstacles due to regulatory weaknesses and the lack of understanding and trust from the parties involved. This research aims to evaluate the effectiveness of the current legal framework for mediation and propose solutions for improvements in order to achieve more equitable conflict resolution. This study employs qualitative methods with both normative and empirical approaches. Data is collected through literature reviews, legal analysis, and interviews with relevant stakeholders such as mediators, employers, and workers. The research findings indicate that although mediation has significant potential in resolving industrial conflicts, weaknesses in implementation and regulatory oversight often render this process suboptimal. Therefore, legal reform is necessary, encompassing the enhancement of mediator capacities, the revision of regulations pertaining to the rights and obligations of the parties, and the strengthening of monitoring and evaluation mechanisms. This reform is expected to improve public trust in mediation and create fair and equitable resolutions for all parties.